Nodular pulmonary histoplasmosis in an immunocompetent tile-cutting worker with poultry farming history: A diagnostic challenge in a non-endemic region of central India - Neha S. Bawankar; Prashant P. Meshram; Swati M. Bhise; Shivaprakash M. Rudramurthy; Sunita Gupta (The Microbe, 2025)
The classic histoplasmosis caused by Histoplasma capsulatum var. capsulatum is a systemic fungal infection primarily affecting immunocompromised patients. Although rare in India, sporadic cases have been reported from various parts of the country. The authors present a case of nodular pulmonary histoplasmosis in an immunocompetent 44-year-old male, tile-cutting worker, non-smoker from a nonendemic region of Central India, who was admitted to the tertiary care hospital with chief complaints of an insidious onset of non-productive cough and shortness of breath for 15 days. He had been involved in poultry farming for 20 years. The patient was clinically misdiagnosed as bacterial/viral pneumonia and radiologically as pulmonary neoplasm. The diagnosis was confirmed through histopathological studies, mycological evaluation of lung tissue specimens, and molecular identification using rDNA Internal Transcribed Spacer sequencing. The patient was started on itraconazole, and his symptoms improved over the following weeks. He was followed up for six months, during which he showed complete resolution of pulmonary nodules. This case highlights the importance of considering histoplasmosis as a differential diagnosis in patients with pulmonary nodules in non-endemic regions. It also emphasizes the need for greater awareness and understanding of the disease's characteristics to facilitate accurate diagnosis and treatment of pulmonary histoplasmosis.